Third trimester maternal 1,25-dihydroxyvitamin D and neonatal birth weight - Yusrawati Yusrawati; Meldafia Idaman; Nur Indrawati Lipoeto (Paediatrica Indonesiana, 2017)
AbstractBackground The main cause of neonatal mortality is low birth weight. Active form of vitamin D (1,25-dihydroxyvitamin D) increase the efficiency of calcium and phosphorous absorption in intestinal. Deficiency 1,25-dihydroxyvitamin D in pregnant woman was hipothesized relates with low birth weight in neonate.Objective To determine the relationship between maternal 1,25-dihydroxyvitamin D level and neonatal birth weight.Methods This was an observational study with cohort design to 47 women in the third trimester pregnancy. This study was cond  ucted on August to December 2014. Subjects were taken from Ibu dan Anak Hospital, Padang, West Sumatera. Maternal blood from antecubital vein was examined for 1,25-dihydroxyvitamin D concentration using enzyme-linked immunosorbent assay (ELISA). Neonatal birth weights were measured right after delivery.  Data were analyzed by Pearson’s correlation and linear regression tests.Results A positive correlation was found between maternal 1,25-dihydroxyvitamin D level and neonatal birth weight (R=0.910; R2=0.821; P=0.000). The 1,25-dihydroxyvitamin D level had an 82.1% contribution to the baby’s birth weight, while other factors not assessed in this study had less of an effect.Conclusion There was positive correlation between maternal 1,25-dihydroxyvitamin D levels in the third trimester of pregnancy and neonatal birth weight